Down and Out in Los Angeles and Berlin : The Sociospatial Exclusion of Homeless People - Von Mahs, Jürgen, 1967- (Book collections on Project MUSE., 2013)
Los Angeles, California, and Berlin, Germany, have been dubbed "homeless capitals" for having the largest homeless populations of their respective countries. In this book, the author provides a comparative analysis of the impact of social welfare policy on homelessness in these cities. He addresses the opportunity of people to overcome - or "exit" - homelessness and shows how Berlin, with its considerable social and economic investment for assisting its homeless, has been as unsuccessful as Los Angeles. Drawing on ethnographic insights, the author shows how homeless people in both cities face sociospatial exclusion - legal displacement for criminal activities, poor shelters in impoverished neighborhoods, and market barriers that restrict reintegration. Providing a wake-up call for readers, this book addresses the critical public policy issues that can produce effective services to improve homeless people's chances for a lasting exit.